Sunnat-i Nabaviyyah aur Qurʼān-i Karīm - Muḵẖtār, Muḥammad Ḥabībullāh (Silsilah-yi ma̤tbūʻāt-i Majlis ad-Daʻvat vat-Taḥqīqulislāmī ;, 1980)
On the significance of Hadith (Isamic traditions) in the light of the Koran.